2011
DOI: 10.1021/ic201440j
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Cu(I) with Selenium-Containing Amino Acids Determined by NMR, XAS, and DFT Studies

Abstract: Cu(I) coordination by organoselenium compounds was recently reported as a mechanism for their prevention of copper-mediated DNA damage. To establish whether direct Se-Cu coordination may be involved in selenium antioxidant activity, Cu(I) coordination of the selenoamino acids methyl-Se-cysteine (MeSeCys) and selenomethionine (SeMet) was investigated. NMR results in D2O indicate that Cu(I) binds to the Se atom of both MeSeCys and SeMet as well as the carboxylic acid oxygen atom(s) or amine nitrogen atoms. X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…The product in 50 mmol scale synthesis was recrystallized from acetone to give a moderate yield (13.79 2 stirring. An additional 6 h was allowed to insure completion of complexation.…”
Section: N-(26-diisopropylphenyl)-nј-benzoylthiourea (L) (1)mentioning
confidence: 99%
See 3 more Smart Citations
“…The product in 50 mmol scale synthesis was recrystallized from acetone to give a moderate yield (13.79 2 stirring. An additional 6 h was allowed to insure completion of complexation.…”
Section: N-(26-diisopropylphenyl)-nј-benzoylthiourea (L) (1)mentioning
confidence: 99%
“…40 [LICu(μ-L)] 2 (5): The procedure for the preparation of 5 was similar to that described for compound 2 using 1 (0.85g, 2.5 mmol) in THF (20 mL) and CuI (0.25 g, 1.3 mmol) in ethanol (20 mL) to afford a yellow precipitate. The solid was separated by filtration and washed with n-hexane (0.4 g, 0.23 mmol, 37 % 2 X-ray Crystallography: Data were collected with a Bruker SMART APEX II CCD diffractometer for 1·THF, 2-5, and 2Ј·2tol and an Oxford Gemini S Ultra system for 1. The diffraction data were obtained by using graphite monochromated Mo-K α radiation with a ω-2θ scan technique at room temperature.…”
Section: N-(26-diisopropylphenyl)-nј-benzoylthiourea (L) (1)mentioning
confidence: 99%
See 2 more Smart Citations
“…In some cancer cells, MeSeCys was largely unmetabolised, with the generation of dimethyldiselenide (DMeDSe) alone suggesting the generation of MeSe – , although MeSeCys was comparatively non-toxic to the cells [13,56]. Tsuji et al [31,57] found that long-term ingestion of MeSeCys by rats led to Se accumulation in the kidney, liver and testes, selenoprotein synthesis and the excretion of TMSe + and selenosugars in urine, in accordance with the prevailing model of Se metabolism [34].…”
Section: The Selenium Speciation Problemmentioning
confidence: 99%